MITIGATING CLIMATE IMPACT: CARBON FOOTPRINT REDUCTION STRATEGIES IN LITHIUM BATTERY RECYCLING FOR SUSTAINABLE ELECTRIC AND HYBRID VEHICLE SUPPLY CHAIN - Wicaksono, Faisal Abror; Sriwardiningsih, Enggal (Journal of Management, Economic, and Financial, 2025)
Lithium-ion batteries used in electric and hybrid cars are explored in this article while keeping in mind the eco-friendly principles and the repercussions. It is critical to highlight that the transition to green energy is accelerating and hybrid cars have a significant role in it. The preferred theory of battery production, however, is fraught with severe complications such as the need for cobalt, nickel, and lithium. The Greenhouse gases associated with these activities are examined concurrently with the environmental damage caused by mining such as ecosystem disruption, contamination of water, and degradation of soil. The article addresses the issues of sustainability which defines emission limits while maximising output, nuanced policies in achieving economic development, social justice and ecological integrity are also discussed in detail. To mitigate this impacts, the article proposes several strategie, including technological innovations in mining practices, enhanced recycling methods, and robust policy recommendationsaimed at promoting sustainable mining. It also reviews existing regulations and their effectiveness in fostering sustainability, suggesting improvements to better align environmental and economic goals. Looking ahead, the article discusses emerging trends in hybrid battery technology, the potential for alternative materials, and the necessity of interdisciplinary approaches to address sustainability challenges. Ultimately, the article calls stakeholders to prioritize sustainable practices in the hybrid battery supply chain, underscoring the importance of balancing environmental impact with greenhouse gas emissions to achieve a more sustainable future